Complexes of Emotions in Joseph and Aseneth. (March 2021) - Smith, Tyler
The ancient Greek novel introduced to the history of literature a new topos : the "complex of emotions." This became a staple of storytelling and remains widely in use across a variety of genres to the present day. The Hellenistic Jewish text Joseph and Aseneth employs this topos in at least three passages, where it draws attention to the cognitive-emotional aspect of the heroine's conversion. This is interesting for what it contributes to our understanding of the genre of Aseneth, but it also has social-historical implications. In particular, it supports the idea that Aseneth reflects concerns about Gentile partners in Jewish-Gentile marriages, that Gentile partners might convert out of expedience or that they might be less than fully committed to abandoning "idolatrous" attachments. The representations of deep, grievous, and complex emotions in Aseneth's transformational turn from idolatry to monolatry, then, might play a psychagogic role for the Gentile reader interested in marrying a Jewish person.